2021
DOI: 10.1159/000515359
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Interleukin-27 in Atherosclerosis: A Contemporary Review

Abstract: Atherosclerosis is a chronic inflammation characterized by an imbalance between inhibitors and stimulators of the inflammatory system that leads to the formation of atherosclerotic plaques in the vessel walls. Interleukin (IL)-27 is one of the recently discovered cytokines that have an immunomodulatory role in autoimmune and inflammatory diseases. However, the definite role of IL-27 in the pathogenesis of atherosclerosis remains unclear. Recent studies on cardiomyocytes and vascular endothelium have demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
19

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 76 publications
0
7
0
19
Order By: Relevance
“…We finally turned to 2 measures that directly determine peak VO 2 : peak exercise CO and extraction (Figure 5B ). ‡ Proteins that displayed higher importance for peripheral O 2 extraction versus peak CO reflect mechanistic processes not confined to the heart: inflammation and oxidative stress (paraoxonase 3 41 ), vascular health and hemostasis (tissue plasminogen activator 51 ), metabolic dysfunction (adenosine deaminase, 31 low‐affinity immunoglobulin gamma Fc region receptor‐II, 50 interleukin‐27 53 ); fibrosis (matrix metalloprotein‐7/10, 47 urokinase plasminogen activator 52 ), and skeletal muscle health and iron metabolism (transferrin receptor protein 1 48 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We finally turned to 2 measures that directly determine peak VO 2 : peak exercise CO and extraction (Figure 5B ). ‡ Proteins that displayed higher importance for peripheral O 2 extraction versus peak CO reflect mechanistic processes not confined to the heart: inflammation and oxidative stress (paraoxonase 3 41 ), vascular health and hemostasis (tissue plasminogen activator 51 ), metabolic dysfunction (adenosine deaminase, 31 low‐affinity immunoglobulin gamma Fc region receptor‐II, 50 interleukin‐27 53 ); fibrosis (matrix metalloprotein‐7/10, 47 urokinase plasminogen activator 52 ), and skeletal muscle health and iron metabolism (transferrin receptor protein 1 48 ).…”
Section: Resultsmentioning
confidence: 99%
“… ‡ References: 17 , 20 , 25 , 31 , 32 , 35 , 41 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 . …”
unclassified
“…In our experiment, a positive correlation between iNOS and NO was observed. A previous study has shown that reducing NO production by inhibiting iNOS can significantly reduce the production of MMPs and IL-1β ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis is one of the major causes of cardiovascular diseases and is characterized by the accumulation of lipids and fibrous plaques in the large arteries, which may lead to heart attacks, strokes, and peripheral vascular diseases [115].…”
Section: Vaccinium and Atherosclerosismentioning
confidence: 99%